Potential Application of ESD-Oriented Differentiated Learning Website on Biotechnology Materials - Prasetyo Anggun Pribadi; Ary Susatyo Nugroho; Muhammad Syaipul Hayat (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
The demands of 21st century learning require teachers to develop learning media that are not only in accordance with student learning needs but also adapt to the era, one of the relevant media alternatives is the website. The purpose of this study was to analyze the potential application of website-based learning media with a differentiated and ESD-oriented approach to Biotechnology material. The method used in this research is descriptive quantitative, the research subjects are 10 biology teachers in Kebumen Regency and 95 students at SMAN 1 Karanganyar, Kebumen Regency. Data collection techniques through questionnaires for teachers and students and document analysis of teacher teaching modules, then analyzed descriptively based on the average value of each indicator. The scale categories are divided into 0-20% very poor, 21-40% poor, 41-60% fair, 61-80% good, and 81-100% very good. The results of the teacher questionnaire analysis showed that the indicators of teacher understanding of differentiated learning obtained an average of 73% (Good), teacher understanding of ESD 72% (Good), teaching habits of teachers 74% (Good), infrastructure conditions 81% (Very Good), and the potential of the Website 90% (Very Good). The results of the analysis of student questionnaires obtained results for the category of student learning habits average 76.3% (Good), habits of using the website 74.8% (Good), and supporting infrastructure 72.1% (Good). The results of the module analysis show that the implementation of differentiated learning is good but the integration of ESD has not been done explicitly. From the results of the analysis, it can be concluded that the development of ESD-oriented differentiated learning websites has the potential to be applied in learning Biotechnology materials.